Comparable Rates of Integrated Myofibrillar Protein Synthesis Between Endurance-Trained Master Athletes and Untrained Older Individuals - McKendry, James; Shad, Brandon J.; Smeuninx, Benoit; Oikawa, Sara Y.; Wallis, Gareth; Greig, Carolyn; Phillips, Stuart M.; Breen, Leigh (Frontiers in Physiology, 2019)
Background An impaired muscle anabolic response to exercise and protein nutrition is thought to underpin age-related muscle loss, which may be exacerbated by aspects of biological aging that may not be present in older individuals who have undertaken long-term high-level exercise training, or master athletes (MA). The aim of this study was to compare rested-state and exercise-induced rates of integrated myofibrillar protein synthesis (iMyoPS) and intracellular signaling in endurance trained MA and healthy age-matched untrained individuals (Older Controls). Methods In a parallel study design, iMyoPS rates were determined over 48 h in the rested-state and following a bout of unaccustomed resistance exercise (RE) in OC (n = 8 males; 73.5 ± 3.3 years) and endurance-trained MA (n = 7 males; 68.9 ± 5.7 years). Intramuscular anabolic signaling was also determined. During the iMyoPS measurement period, physical activity was monitored via accelerometry and dietary intake was controlled. Results Anthropometrics, habitual activity, and dietary intake were similar between groups. There was no difference in rested-state rates of iMyoPS between OC (1.47 ± 0.06%⋅day–1) and MA (1.46 ± 0.08%⋅day–1). RE significantly increased iMyoPS above rest in both OC (1.60 ± 0.08%⋅day–1, P < 0.01) and MA (1.61 ± 0.08%⋅day–1, P < 0.01), with no difference between groups. AktThr308 phosphorylation increased at 1 h post-RE in OC (P < 0.05), but not MA. No other between-group differences in intramuscular signaling were apparent at any time-point. Conclusion While our sample size is limited, these data suggest that rested-state and RE-induced iMyoPS are indistinguishable between MA and OC. Importantly, the OC retain a capacity for RE-induced stimulation of skeletal muscle remodeling.